Interplay between surfactant self-assembly and adsorption at hydrophobic surfaces: insights from dissipative particle dynamics. (18th August 2021) - Šindelka, Karel; Lísal, Martin
ABSTRACT: We study the self-organisation of aqueous surfactants in bulk phase, and the adsorption and self-organisation of the aqueous surfactants at a planar hydrophobic surface by dissipative particle dynamics. Nonionic surfactants, n -alkyl poly(ethylene oxide) C n E m, and water are coarse-grained into mesoscopic beads comprising 1–3 heavy atoms and two water molecules, respectively. The size of the mesoscopic beads is related to the molar volume of the underlying molecular fragments while the bead–bead interaction parameters are calibrated against the water-octanol partition coefficients. We focus on the C 6 E 3, C 6 E 4, C 8 E 3, and C 8 E 4 surfactants in water that form spherical micelles in the bulk. The bulk micellization is primarily affected by the alkyl tail length which is demonstrated by an order of magnitude decrease in the critical micelle concentration when going from the aqueous C 6 E m to aqueous C 8 E m solutions. Surfactants strongly adsorb on the hydrophobic surface, adopting lying-down configurations and forming hemispheres which are in equilibrium with the spherical micelles in the bulk. In contrast to the bulk phase, the surfactant adsorption behaviour is influenced by both the alkyl tail and head chain lengths. GRAPHICAL ABSTRACT: UF0001